Unraveling Metagenomics: A Comprehensive Diagnostic Approach for COVID-19 - Lavanya T. Nair; Shweta Singh (International Journal of Tropical Medicines, 2024)
The COVID-19 pandemic has brought attention to the need for rapid, accurate, and scalable diagnostic techniques. Metagenomics, a powerful technique that enables the comprehensive analysis of genetic material from complex microbial communities, has emerged as a promising diagnostic approach for COVID-19. This article elucidates the principles of metagenomic sequencing, highlighting its ability to detect viral RNA directly from clinical samples without prior knowledge of the pathogen. Furthermore, we discuss the advantages of metagenomics over traditional diagnostic methods, including its ability to identify emerging viral variants and co-infections. Additionally, we explore the challenges and limitations associated with metagenomic diagnostics, such as bioinformatics complexity and cost considerations. Moreover, we review recent advancements in metagenomic technologies and their applications in COVID-19 surveillance, outbreak monitoring, and vaccine development. Finally, we discuss future perspectives and the potential integration of metagenomics into routine clinical practice, emphasizing its role in shaping the future of infectious disease diagnosis and management.
Keywords: Bioinformatics; COVID-19 diagnostics; Metagenomics; Surveillance; viral variants